performance of the unsignalized intersection of Jenderal Suprapto-S. Parman road. - Pinggungan, Fica; Purba, Aleksander; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
With the increase in population and increasing the number of private vehicle ownership, it will cause traffic problems due to the many movements of community mobility, one of which is at the intersection. Bandar Lampung is one of the developing cities that experience these problems. One of the intersections in Bandar Lampung to be reviewed is the unsignalized intersection with 4 arms on Jendral Suprapto-S. Parman road. The purpose of this study is to evaluate and compare the performance of the intersection of Jenderal Suprapto-S. Parman road. Then the results of the analysis using KAJI are capacity (C) 2735 pcu / hour, degree of saturation (DS) 1.12, delay deviation (D) 43.01 sec / pcu and queuing probability (QP%) 60% - 122% with level service C. Analysis with the VISSIM program is a delay of 3.35 seconds / pcu (North), 5.4 seconds / pcu (West), 68.29 seconds / pcu (South), 33.89 seconds / pcu (East), while for long queue 31.68 m (North), 23.98 m (East), 190.3 m (South) and 31.13 m (West) with service level B. While the results of the Queue Theory analysis a delay of 49 seconds / pcu ( North), 39.2 seconds / pcu (West), 72.8 seconds / pcu (South) 124 seconds / pcu (East), while the queue length is 50 m (North), 63 m (East), 40 m (South ) and 25 m (West).